Angiopteris cochinchinensis de Vriese Ameliorates LPS-Induced Acute Lung Injury via Src Inhibition - Won Young Jang; Hwa Pyoung Lee; Seung A Kim; Lei Huang; Ji Hye Yoon; Chae Yun Shin; Ankita Mitra; Han Gyung Kim; Jae Youl Cho (Plants, 2022)
Growing demand for treatment options against acute lung injury (ALI) emphasizes studies on plant extracts harboring anti-inflammatory effects. According to GC-MS analysis, Angiopteris cochinchinensis de Vriese consists of various flavonoids with anti-inflammatory activities. Thus, in this study, the anti-inflammatory effects of an extract of Angiopteris cochinchinensis de Vriese (Ac-EE) were assessed using RAW264.6 murine macrophages and a lipopolysaccharide (LPS)-induced ALI model. Ac-EE reduced the nitric oxide production in murine macrophages increased by LPS induction. Moreover, protective effects of Ac-EE on lung tissue were demonstrated by shrinkage of edema and lung injury. Reduced neutrophil infiltration and formation of hyaline membranes were also detected in lung tissues after H&E staining. Semiquantitative RT-PCR, quantitative real-time PCR, and ELISA showed that Ac-EE inhibits the production of proinflammatory mediators, including iNOS and COX-2, and cytokines, such as TNF-α, IL-1β, and IL-6. An Ac-EE-mediated anti-inflammatory response was derived from inhibiting the NF-κB signaling pathway, which was evaluated by luciferase reporter assay and Western blotting analysis. A cellular thermal shift assay revealed that the prime target of Ac-EE in alleviating inflammation was Src. With its direct binding with Src, Angiopteris cochinchinensis de Vriese significantly mitigates lung injury, showing possibilities of its potential as an effective botanical drug.